Comparison of Artificial Water Pump Drive Models - Zuraida, Ida; Pramudya Kurniawan; Wattini (Politeknik Negeri Jakarta, 2024)
Starting from a printed water filter that uses an electric water pump, we tried to make a breakthrough by making an artificial pump using wind energy. Wind energy requires an appropriate drive model. Two driving models were tried and then compared between the two to get the best model to be applied as a recommendation for the wider community. In the initial stage, model design was carried out, both an artificial pump model and a driving model with two variations. Next, prepare the necessary materials, then make the model. For pump models from PVC pipes, drive models from plastic drums and drive models from mineral bottles as well as supporting system models. The supporting system is a network of intake pipes to the pump system and from the pump to the reservoir. Then the final step is to make a tower model from light steel with a height of approximately 10 meters. All models made such as custom pumps and drive models need to be tested to ensure whether the model can function properly. Apart from that, it is also necessary to evaluate if there are obstacles so that it can function optimally. Next, data collection and analysis of existing data is carried out. The final step is to draw a conclusion regarding the model being made and choose the best drive model with all its advantages and disadvantages. Based on nine trials by rotating the drive models (2 models) manually, a conclusion can be drawn that Drive Models 1 and 2 can rotate well, the crank also functions well and the artificial pump after evaluation is finally functional and able to drain as much water as possible. 0.38 liters per one revolution of the drive model. The volume of water obtained is the maximum capacity based on a comparative calculation of the volume of the pump tube of 0.34 liters. Both Drive Models can be raised to a higher level of 5 meters or 10 meters for strong wind gusts. However, because the area where the research was conducted, the wind gusts were protected by tall buildings, so the results were not optimal.